Flux distribution of the Superphénix start-up core for the validation of neutronic codes. (November 2019) - Garcia, E.; Sciora, P.; Kooyman, T.; Rimpault, G.; Guo, H.; Faure, B.
Highlights: The Superphénix fission rate is analyzed with stochastic and deterministic codes. Deterministic codes show a good agreement with stochastic evaluations and measurements. Considerations made with ERANOS code do not imply large deviations on flux distribution. No considerable difference is found when switching from JEFF 3.1.1 and JEFF 3.2. The modeling with APOLLO-3 provides more flexibility for complex geometries. Abstract: The Superphénix reactor remains the largest Sodium-cooled Fast Reactor (SFR) ever built in the world and its legacy is a unique source of information for SFRs. At the Superphénix start-up, a series of tests (Transversal Irradiation tests) were devoted to the core flux distribution with measurements in several assembly positions located from the core center to its periphery. On the other hand, the recent development of neutronic codes has improved accuracy and it is worthwhile to try reproducing these tests. The APOLLO-3 code, for instance, can treat complex geometries without substantial approximations. In this paper, the Superphénix radial and axial flux profiles are assessed for two Transversal irradiation tests, with a reference Monte Carlo code (TRIPOLI-4) and two deterministic codes, the ERANOS code and its successor the APOLLO-3 code. In a first time, a numerical validation between codes is done to observe the deterministic code bias on the fission rate by comparing the ERANOS and APOLLO-3 evaluations to the TRIPOLI-4 model. Good agreement is seen between codes, and discrepancies between ERANOS and APOLLO-3 remain limited. However, the use of APOLLO-3 eliminates any potential fission rate bias due to the possible compensating errors at the assembly step calculation. An additional survey on the fission rate variations between the JEFF 3.1.1 and the JEFF 3.2 with the same code shows that minor differences are found for the Transversal irradiation tests. It can be concluded that current computational tools are relevant for predicting core flux distribution.